Effects of zinc deficiency and supplementation on plasma leptin levels in rats - Baltaci, AK; Mogulkoc, R; Halifeoglu, I (Humana Press Inc, 2005)
The effects of zinc deficiency and supplementation on plasma leptin levels were studied in Sprague-Dawley rats. After 6 wk on a zinc-deficient diet containing 0.65 ppm Zn/g, the mean body weight was significantly lower than that of normal or zinc-supplemented rats, which showed no difference among them. The plasma leptin and zinc levels were lowest in zinc-deficient animals and highest in those that received a normal diet and daily intraperitioneal injections of 3 mg Zn/kg. These results indicate that zinc deficiency leads to a significant inhibition in plasma leptin levels, whereas zinc supplementation significantly increases plasma leptin.
Keywords: zinc deficiency and supplementation; leptin, rat